Effects of carbonaceous nanofillers on the mechanical and electrical properties of crosslinked poly(cyclooctene). Issue 5 (21st September 2016) - Dorigato, A.; Pegoretti, A.
Abstract : In this work the mechanical and electrical behavior of poly(cyclooctene) (PCO)‐based nanocomposites were investigated. At this aim, different amounts (0.5–4 wt%) of carbon black (CB), carbon nanofibers (NF) and exfoliated graphite nanoplatelets (xGnP) were melt compounded with a PCO matrix and crosslinked with dicumylperoxide (DCP). The progressive increase of the DCP concentration led to an evident decrease of both the melting temperature and the crystallization temperature, and also the relative crystallinity was strongly reduced. Microstructural observations on nanocomposites materials with a DCP amount of 2 wt% evidenced how CB nanocomposites were characterized by a good nanofiller dispersion within the matrix, while NF and xGnP nanofilled samples presented a more aggregated morphology. The introduction of CB and xGnP determined an enhancement of the elastic modulus of the material, without impairing the ultimate properties of the pristine matrix. Electrical resistivity measurements evidenced how the prepared composites can be interesting as electro‐active materials for CB concentrations higher than 2 wt%. POLYM. ENG. SCI., 57:537–543, 2017. © 2016 Society of Plastics Engineers